2003
DOI: 10.1590/s0101-81752003000200029
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Brazilian species of Pelecitus Railliet & Henry (Nematoda, Filarioidea) with the establishment of new records

Abstract: and Pelecitus sp., are presented, with basis on 29 nematode samples recovered from Brazilian birds representing 13 families and 19 species that were captured between 1934-1951 in the southeastern and central regions; parasites were formerly deposited as unidentified material in the Helminthological Collection of the Oswaldo Cruz Institute.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 5 publications
2
11
1
2
Order By: Relevance
“…The new knowledge about the internal presence of the nematode contradicts what was reported by Pinto and Noronha (2003) and Bartlett (2009) in other bird species. This brings up an important question that needs to be considered, i.e.…”
Section: Introductioncontrasting
confidence: 62%
See 2 more Smart Citations
“…The new knowledge about the internal presence of the nematode contradicts what was reported by Pinto and Noronha (2003) and Bartlett (2009) in other bird species. This brings up an important question that needs to be considered, i.e.…”
Section: Introductioncontrasting
confidence: 62%
“…The genus Pelecitus has 160 species that infect mammals and, especially, birds (BARTLETT, 2009 alcohol and clarified in phenol for identification, which was done using a computerized image analysis system (Leica). The nematodes collected were both females, and were in the genus Pelecitus (Figure 1), according to Vicente et al (1995) and Pinto and Noronha (2003). Voucher parasite specimens were deposited in the helminthological collection of the Institute of Biosciences, São Paulo State University, Botucatu, São Paulo, Brazil, under the number CHIBB 7174.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is one record for this helminth for Falco tinnunculus Linnaeus 1758 (Falconiformes, Falconidae) from The Netherlands (Borgsteede et al, 2003). In Chile P. caudinfl ata has been diagnosed in Columba livia Gmelin 1789 (Columbiformes, Columbidae) from Valdivia (Pazmiño, 2007). This nematode has an indirect life cycle with earthworms as intermediate host (Yabsley, 2008).…”
Section: Capillaria Tenuissimamentioning
confidence: 99%
“…Different bird families have been reported as hosts of P. fulicaeatrae, including grebes (VANDERBURGH et al, 1984;BARTLETT & GREINER, 1986;BARTLETT & ANDERSON, 1989;ESCUDERO et al, 2007). In South America, the occurrence of P. fulicaeatrae was previously reported in the gray-necked wood-rail Aramides cajanea (Rallidae) and in the jabiru Jabiru mycteria (Ciconiidae) in Brazil (PINTO & NORONHA, 2003). Escudero et al (2007) reported the first record of P. occipitalis from Argentina.…”
Section: Resultsmentioning
confidence: 91%